A new method for calculating highway blocking due to high-impact weather conditions - D. Liu; T. Jing; T. Jing; T. Jing; M. Yan; I. Gultepe; Y. Bao; Y. Bao; Y. Bao; H. Wang; F. Zu (Natural Hazards and Earth System Sciences)
Fog, rain, snow, and ice are the high-impact weather events that often lead to highway blockings, which in turn causes serious economic and human losses. At present, there is no clear calculation method for the severity of highway blocking, which is related to highway load degree and economic losses. Therefore, there is an urgent need to propose a method for assessing the economic losses caused by high-impact weather events that lead to highway blockages, in order to facilitate the management and control of highways and the evaluation of economic losses. The goal of this work is to develop a method to be used to assess the high-impact weather (HIW) effects on highway blocking. Based on the K-means cluster analysis and the CRITIC (criteria importance through intercriteria correlation) weight assignment method, we analyzed the highway-blocking events that occurred in Chinese provinces in 2020. Through cluster analysis, a new method of severity levels of highway blocking is developed to distinguish the severity into five levels. The severity levels of highway blocking due to high-impact weather are evaluated for all weather types. As a part of calculating the degree of highway blocking, the highway load in each province is evaluated. The economic losses caused by dense fog are specifically assessed for the entire country.